Long-Term Safety of Rapid Daratumumab Infusions in Multiple Myeloma Patients - Gozzetti, Alessandro; Bacchiarri, Francesca; Sammartano, Vincenzo; Defina, Marzia; Sicuranza, Anna; Mecacci, Bianca; Zappone, Elisabetta; Cencini, Emanuele; Fabbri, Alberto; Raspadori, Donatella; Bocchia, Monica (Frontiers in Oncology, 2020)
Multiple myeloma survival has significantly improved in recent years, due to novel agents that are available for treatment. The anti-CD38 monoclonal antibody Daratumumab is particularly efficient for patients with relapse/refractory disease, and many studies have shown its unprecedented efficacy also as a first treatment. However, to avoid the incidence of infusion reactions, long infusion schedules of 8 hours at first dose and 4 hours in the following doses are required, which can reduce the compliance of patients and health care professionals. A reduced infusion time of 90 minutes has been reported previously, but data are missing on the prolonged safety of this over time as well as the efficacy of this approach. In this work, we investigate the safety of 484 rapid Daratumumab infusions given early after the second dose over a 22 month period in 39 myeloma patients.